Justification of the microcutting scheme in the friction-mechanical method of applying anti-friction coatings - Shepelenko, I.V.; Nemyrovskyi, Ya.B.; Chernovol, M.I.; Krasota, M.V.; Vasylenko, I.F. (Problems of Tribology, 2026)
A review of modern approaches to substantiating the patterns of anti-friction coating formation during friction-mechanical application has made it possible to establish the importance of ensuring favourable conditions for microcutting of anti-friction material. Creating these conditions requires studying the interaction scheme of microirregularities in the contact zone between the tool and the part. From the point of view of cutting mechanics, a scheme of interaction of a single micro-irregularity, which is a model – a cutter made of 200 gray cast iron, with a contact surface made of anti-friction material – brass L63, was constructed, which made it possible to establish physical changes in the tool and machined surface system. The value of the front cutting angle has been theoretically established to ensure maximum efficiency of the microcutting process and filling of microcavities between microirregularities. The use of a model experiment, the method of similarity and dimensions made it possible to confirm the main theoretical regularities obtained using characteristic microcutting diagrams. It has been shown that the process of changing the geometry of the micro-irregularity vertex occurs in accordance with the principle of adaptability of the entire ‘tool-part’ system, according to which the minimum micro-cutting energy is realised. The results obtained are an important reserve for improving the quality of anti-friction coating application by the friction-mechanical method